Legal Education About Efforts to Resolve Domestic Violence Against Wives - Sopacua, Margie Gladies; Taufik, Iqbal; Latumerissa, Denni (AIWADTHU: Jurnal Pengabdian Hukum, 2025)
Introduction: Domestic violence, especially against wives, is a legal event that we often encounter in Indonesian society. Violence against wives that occurs in the household is not only experienced and found in the public sphere, but also very prevalent in the domestic sphere.Purposes of The Devotion: Providing Understanding to the Community, Community Service in Waipirit Village, Kairatu District, West Seram Regency, about Domestic Violence and efforts to resolve domestic violence crimes experienced by wives can be done using a restorative justice approach. Method of The Devotion: The method used is legal counseling to the community about efforts to resolve domestic violence crimes experienced by wives can be carried out using the Western restorative justice approach in Waipirit Village, Kairatu District, West Seram Regency.Results Main Findings of the Devotion: The implementation of Community Service activities  in Waipirit Village, Kairatu District, West Seram Regency,  can be found in efforts to resolve  domestic violence crimes experienced by wives can be carried out using a restorative justice approach where it provides opportunities for  parties  who are involved, especially the perpetrator and the victim, to participate in solving the case in such a way that the  role of the perpetrator and victim here only acts as witnesses when the case of violence is resolved by the police, especially in the Child Protection Law.